Metallurgical activity in the area of Teatro alla Scala in Milan (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The paper focuses on the description of some molds for the casting of small bronze objects, found in a workshop area of the Roman Mediolanum, casually discovered during the renovation works of Teatro alla Scala. The finding of crucibles, made of common pottery vessels covered with a heavy layer of clay, allows a dating to the early imperial age.
Keywords: Mediolanum; metallurgical activity; molds; early imperial age